A Comparative Study of Vitrectomy Combined with Internal Limiting Membrane Peeling for the Treatment of Idiopathic Macular Hole with Air or C3F8 Intraocular Tamponade - Xiang Chen; Yi Yao; Xiaolu Hao; Xiaocui Liu; Tiecheng Liu (Journal of Ophthalmology)
Purpose. The treatment of idiopathic macular holes has been basically modeled, and vitreoretinal surgery is recognized as an effective treatment. However, the postoperative tamponade of gas will still make the patient uncomfortable and may have related complications. The purpose of this study is to investigate whether air as an intraocular tamponade is equivalent to gas and what advantages may exist. Methods. A retrospective study was performed in one hundred and ninety-eight patients from 2013 to 2017; 112 received gas tamponade and 86 received air tamponade. After receiving retinal surgery, the outcomes of best corrected visual acuity, intraocular pressure, slit lamp examination, fundus examination, and imaging of the macula by spectral-domain optical coherence tomography were analyzed. Results. Before operation, there was no statistically significant difference in age, sex, macular hole diameter, or visual acuity between groups. The median follow-up period for the C3F8 group was 26 months, and the median follow-up for the air group was 25 months. After the operation, the best corrected visual acuity and macular hole closure rate were not significantly different between the two groups. The face-down time after the operation, the incidence of lens opacity on the third postoperative day, the intraocular pressure on the third postoperative day, and the operation time were significantly different between the two groups. Conclusions. In idiopathic macular hole surgery, the effect of air as an intraocular tamponade material can be similar to that of C3F8 but has fewer complications. In particular, it is a better choice for patients for whom the face-down position is not suitable.